OTT Enchantment: Decoding the Secret of Millennial’s Subscription Intentions - Sinha, Deepti; Sinha, Sachin; Phutela, Nidhi; Grover, Priya (International Review of Management and Marketing, 2024)
This study explores the factors that affect intention and choices of millennials for subscription of Over-The-Top (OTT) platforms. The study involved a mixed-methods approach, involving exploratory and descriptive design. The outcome of the study showed that there is a profound impact of demographic variables on the subscription intention. Results also indicated that factors like convenient navigation, information seeking, and binge- watching impacted respondents’ attitudes towards purchasing OTT subscriptions. Moreover, factors like relaxation and voyeurism impacted respondents’ attitudes towards continuing OTT subscriptions. The research findings will be helpful for OTT companies to implement new distribution strategies with mobile operators to launch novel services like mobile-only packs and sachet pricing and thereby increase their user base. The study contributes significantly in understanding the viewership and subscription patterns of millennials. The study is exclusively an original contribution of the authors.